Quality control analysis of Best Fried Chicken (BFC) products in Prabumulih City (Lighthouse Publishing, 2023)
The development of an increasingly advanced era requires all business people to innovate, maintain and improve the quality of their respective products. Best Fried Chicken (BFC) is a company engaged in the culinary field that sells fast-food fried chicken products with a partnership system in its business activities. Best Fried Chicken (BFC) Prabumulih City always pays attention to the quality of its products by controlling their quality. However, customers often still need to give more favourable comments about the quality of fried chicken products at Best Fried Chicken (BFC) in Prabumulih City. One way to control product quality is with Statistical Process Control (SPC). This study aims to analyze whether the product quality control at Best Fried Chicken (BFC) in Prabumulih City is still within tolerance limits and to determine the causal factors that affect the quality of the product. The products studied were fried chicken products produced from January 4th to February 2nd, 2023, with the result that the level of damage was still within tolerance limits. According to the cause and effect diagram, the main damage factor is people, methods, and raw materials. The most dominant product damage among the types of scorch damage, inappropriate size, and hard texture is damage to the size that does not match the most dominant causal factors found in humans and methods. Quality control at Best Fried Chicken (BFC) in Prabumulih City can be further improved from all aspects, both humans and the methods used, so that that product damage can be minimized and quality control can run effectively.